2020
DOI: 10.5902/1980509839899
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for determining classes of forest fire risk using the modified Monte Alegre Formula

Abstract: O objetivo deste estudo foi calcular a Fórmula Modificada de Monte Alegre (FMA⁺) e ajustar as classes de risco de incêndio em áreas de florestas plantadas na costa norte-central do estado do Espírito Santo e na costa sul do estado da Bahia. A metodologia utilizada incluiu seis etapas: cálculo de risco; desenvolvimento de planilhas de acordo com a ocorrência, ou não, de incêndios florestais; desenvolvimento de planilhas de acordo com a estação de incêndios florestais na região estudada; definição de classe de r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Other studies have found the benefit of using time lags beyond 2 months, such as the Monte Alegre formula [105,106], the Telicyn Logarithmic Index [107], and the Nesterov index [108], that use the consecutive number of days without rainfall at longer time periods. Also, the Risco do Fogo index, which considers precipitation over a period of 120 days [109].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found the benefit of using time lags beyond 2 months, such as the Monte Alegre formula [105,106], the Telicyn Logarithmic Index [107], and the Nesterov index [108], that use the consecutive number of days without rainfall at longer time periods. Also, the Risco do Fogo index, which considers precipitation over a period of 120 days [109].…”
Section: Discussionmentioning
confidence: 99%